Spontaneous unilateral exudative retinal detachment as the first manifestation of lung cancer - Modrzejewska, Anna; Krzystolik, Karol; Lubiński, Wojciech; Modrzejewska, Monika (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
The authors presented a case of a 50-year-old woman with vision deterioration in the right eye lasting for 3 weeks, without concomitant organ symptoms. Eye fundus examination showed two large bullae of the detached retina, without a visible tear. Fluorescein angiography revealed fluorescein leakage around retinal vessels and dye release in detachment borders in the venous phase. Laboratory tests ruled out parasite, inflammatory and infectious diseases. Chest X-ray with central nervous system and abdominal cavity imaging (Computed Tomography, Magnetic Resonance Imaging) showed disseminated lung tumour with metastases to the brain. Histological evaluation confirmed disseminated lung adenocarcinoma T2N3M1. Spontaneous unilateral exudative retinal detachment, without any chorioretinal metastases may be the first ocular sign of disseminated malignancy.